A simple dihydrophenazine-based chemosensor for the detection of sulfite with turn-on fluorescence. (January 2019) - Li, Yiru; Shi, Lijiang; Zhang, Yiyao; Sun, Guangchen; Sun, Lu; Su, Jianhua
Abstract: A simple novel dihydrophenazine-based chemosensor R has been developed for the detection of SO3 2− in DMSO-H2 O solution with turn-on fluorescence. Upon the addition of sulfite, the ICT (intramolecular charge transfer) system of the probe was destroyed owing to the nucleophilic addition of sulfite to the formyl group of R . Thus a charming orange-red fluorescence centered at 603 nm appeared, which is favorable for potential biosensing. The reaction mechanism was confirmed by MS and 1 H NMR titration. In addition, the detection limit for sulfite was determined as low as 71.4 nM, which is superior to many reported probes. All above results promote the probe as a promising candidate in practical and biological applications. Graphical abstract: Image 1 Highlights: A simple novel dihydrophenazine-based chemosensor R has been synthesized for the detection of SO3 2− . The probe has a charming turn-on orange-red fluorescence centered at 603 nm. The detection limit for sulfite was determined as low as 71.4 nM.